LABOR AND RURAL FARMS IN COLONIAL BUENOS AIRES (1726-1756) - Pelozatto Reilly, Mauro Luis (2016)
This research seeks to analyze and characterize the properties and production practices in colonial Buenos Aires in the first half of the eighteenth century. In addition, we will try to deal with the issue from a local and regional perspective, taking as central livestock production and mixed neighborhoods to see the different situations of rural labor and the characteristics of agricultural and livestock activities during the period 1726-1756.